Genetic analysis of the human malaria parasite plasmodium falciparum - Walliker, D.; Quakyi, I.A.; Wellems, T.E.; McCutchan, T.F.; Szarfman, A.; London, W.T.; Carter, R. (Science, 1987)
Malaria parasites are haploid for most of their life cycle, with zygote formation and meiosis occurring during the mosquito phase of development. The parasites can be analyzed genetically by transmitting mixtures of cloned parasites through mosquitoes to permit cross-fertilization of gametes to occur. A cross was made between two clones of Plasmodium falciparum differing in enzymes, drug sensitivity, antigens, and chromosome patterns. Parasites showing recombination between the parent clone markers were detected at a high frequency. Novel forms of certain chromosomes, detected by pulsed-field gradient gel electrophoresis, were produced readily, showing that extensive rearrangements occur in the parasite genome after cross-fertilization. Since patients are frequently infected with mixtures of genetically distinct parasites, mosquito transmission is likely to provide the principal mechanisms for generating parasites with novel genotypes.